Who Should Be Involved: Unravelling the Concept of ‘Interest in Content Material’ in the Establishment of Laws in Indonesia - Fathimah Azzahro; Riris Ardhanariswari; Muhammad Fauzan; Enny Dwi Cahyani; Tenang Haryanto (Jurnal Hukum dan Pembangunan Ekonomi, 2026)
Article 96 of Law Number 13 of 2022 concerning the Second Amendment to Law Number 12 of 2011 on the Establishment of Legislation (hereinafter referred to as the Law 13/2022).  requires the involvement of interested parties concerning the content matter without clear criteria, resulting in inconsistent selection and weighting of inputs. This study develops a framework of 'interest in content material' as a measure of participation quality as a novelty because no similar research has been concusted before. Given this urgency, this research aims to analyze the institutionalization of public participation and the regulation of stakeholder involvement in law-making in Indonesia, as well as to construct an ideal regulation of the phrase 'interest in content matter' regarding stakeholder involvement in the formulation of laws in Indonesia. This is a normative legal study that employs a conceptual approach, a statutory approach, and a comparative approach. The research results indicate that public participation, particularly the involvement of stakeholders in the formation of legislation, should guarantee the right to provide input at every stage; however, the mechanism is merely formal. Although Law 12/2011 explicitly guarantees space for stakeholders who have an interest in the substance of regulations, its implementation is hindered by three factors: difficulties in identifying groups with substantial interests, lack of transparency in the consultation process, and limited access and capacity of the public, resulting in participation often being symbolic.